The insane and his narrative representations in the novel A Space for Insanity - . Raad Heuer Sweilem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The Iraqi novel has witnessed a remarkable development, and a continuousincrease The Iraqi novelist’s achievement witnessed several transformations, whether at the level of the topics it presented or at the level of pioneering new areas of experimentation, and the novel is the most important narrative art among all the narration arts. It is due to its distinctive architecture, and its uniqueness, in addition to being better able to portray people's concerns and address their social problems. The narrative text represents a large arena in which contradictory ideas, multiple philosophies, and many opinions converge. Due to the complexity of the events expressed on the one hand, and the multiplicity of conflicting personalities on the other hand